Access to literacy skills training as a pathway to better jobs for poor urban youths (2019)
Literacy skill are all the skills needed for reading and writing. Literacy is not merely the ability to read and write, but is a major vehicle for holistic social change and community development. Youths are very important stakeholders in any society. They are not only the future hope of Nigeria, but also major stakeholders and very useful resources in nation building. There is a great need for youths, especially the urban youths to engage in a form of education that seeks to equip them with capacities, skills, knowledge and understanding in specific skills to enable them become productive citizens of their nations and also to enable the them live productive and meaningful lives. This study therefore aims at examining access to literacy skills training as a pathway to better jobs for poor urban youths. Literacy skill training emerged as a proactive response to the practical needs of and challenges facing poor households. It promotes literacy among learners through developmental activities that address their basic and practical needs, thus helping them to break out of the cycle of poverty. The study concludes and recommends that access to literacy skill and training will make urban youths to be self-reliant, therefore government and private sectors should seek the promotion of skills acquisition.